World revolutionary elites : - edited by Harold D. Laswell and Daniel Lerner. (M.I.T. Press, 1965)
With the exception of chapters 1 and 7 and much of chapter 2, the text is reproduced from Hoover Institute studies, 1951-52, and from the American political science review, v. 31. Introduction: The study of political elites, by H. D. Lasswell.--The world revolution of our time: A framework for basic policy research, by H. D. Lasswell.--The Politburo, by G. K. Schueller.--The Fascists: the changing elite, by H. D. Lasswell with R. Sereno.--The Nazi elite, by D. Lerner with I. de S. Pool, and G. K. Schueller.--Kuomintang and Chinese Communists elites, by R. C. North with I. de S. Pool--The coercive ideologists in perspective, by D. Lerner.